Endogenous lung stem cells for lung regeneration. (3rd June 2019) - McQualter, Jonathan L.
ABSTRACT: Introduction : Lifelong maintenance of a healthy lung requires resident stem cells to proliferate according to tissue requirements. Once thought to be a quiescent tissue, evolving views of the complex differentiation landscape of lung stem and progenitor cells have broad implications for our understanding of how the lung is maintained, as well as the development of new therapies for promoting endogenous regeneration in lung disease. Areas covered : This review collates a large body of research relating to the hierarchical organization of epithelial stem cells in the adult lung and their role in tissue homeostasis and regeneration after injury. To identify relevant studies, PubMed was queried using one or a combination of the terms 'lung', 'airway', 'alveoli', 'stem cells', 'progenitor', 'repair' and 'regeneration'. Expert opinion : This review discusses how new technologies and injury models have challenged the demarcations between stem and progenitor cell populations.